THE ROLE OF SONGS AND MUSICS FOR KINDERGARTEN LEARNERS IN LEARNING ENGLISH LANGUAGE - Xolboyeva Sabohat Sherali qizi; Mahkamova Mahliyo; Matenova Feruza Maxamatali qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
ANNOTATION. This study explores the significance of songs and music in enhancing English language acquisition among kindergarten learners. Research indicates that music-based learning engages young children by making the learning process enjoyable, interactive, and memorable. Songs help develop listening skills, improve pronunciation, and reinforce vocabulary retention. Additionally, rhythm and melody aid in cognitive development and emotional engagement, making it easier for children to grasp linguistic patterns and sentence structures. The study also examines the impact of music on motivation, social interaction, and overall language fluency. Findings suggest that incorporating songs in early language education fosters a positive learning environment and enhances linguistic competence among young learners.